Integrasi Nilai-Nilai Islam dalam Dunia Pendidikan: Menjawab Tantangan, Merancang Strategi - Intan Suci Ramadani; Ratna Sri Wahyuni; Gusmaneli (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This article explores the integration of Islamic values in the educational sphere by examining the concept of values, types of Islamic educational values, implementation strategies, and the challenges faced in the process. Islamic values such as honesty, responsibility, compassion, and justice are central to shaping holistic student character. The study uses a literature review method, drawing from relevant academic journal sources. Integration strategies include curriculum-based approaches, school culture, teacher modeling, and value-based learning methodologies. The findings highlight several major challenges, including a lack of comprehensive understanding among educators, the influence of globalization and secular media, and weak collaboration between schools, families, and communities. Furthermore, current national educational policies often do not fully support the inclusion of Islamic values across all subjects. Addressing these issues requires collaborative efforts, continuous teacher development, and contextual strategies to ensure Islamic values are effectively embedded in educational practices. This article contributes to the conceptual understanding of Islamic character education and emphasizes the importance of aligning pedagogy with religious values in the modern educational system.